2019
DOI: 10.1590/1980-5373-mr-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging Temperature, Time, and Pre-Strain on Mechanical Properties of AA7075

Abstract: Aluminum alloys of the 7xxx series (AA7075) are preferred in the aerospace and automotive industries due to their low densities, high strength, good corrosion resistance properties. Additionally, these alloys show the most effective aging properties among aluminum alloys. For this reason, it is very important to determine the most appropriate aging parameters for microstructural development. Literature review reveals that the effect of pre-strain on springback has not been studied yet. In this study, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…2 mm kalınlığında 7075-T6 malzemesine farklı sıcaklık ve sürelerde yaşlandırma işlemi uygulanarak mekanik özelliklerin değişimi daha önceki çalışmamızda incelenmişti [21]. Bu yapılan çalışmada ise, yayınlanan çalışmadaki deneysel veriler kullanılmıştır.…”
Section: Malzeme Ve Yöntemunclassified
“…2 mm kalınlığında 7075-T6 malzemesine farklı sıcaklık ve sürelerde yaşlandırma işlemi uygulanarak mekanik özelliklerin değişimi daha önceki çalışmamızda incelenmişti [21]. Bu yapılan çalışmada ise, yayınlanan çalışmadaki deneysel veriler kullanılmıştır.…”
Section: Malzeme Ve Yöntemunclassified
“…Gao et al [17] have conducted experiments to know the influence of ageing on the tensile strength and microstructure of aluminum alloy 6063, which are treated under different preageing conditions at 165°C, 185°C and 205°C for a range of 25 to 64 hours). Kilic et al [18] have studied the effects of aging temperature and time on AA 7075 and noticed reduction in the yield stress value under increased aging temperature. They also mentioned that AA7075 with T6 temper under dissolved state is evident to brittle fracture with higher hardness value.…”
Section: Introductionmentioning
confidence: 99%
“…Barsom [25] have observed that for the structures operating at higher temperatures with T 4 and T 6 tempered alloys and revealed that both mechanical and physical properties of T6 tempered alloy has higher strength, and low ductility compared to T4 tempered alloy, Kilic [26] have studied the effects of aging temperature, time, and pre-strain on mechanical properties for AA7075 and observed the increased strength under the distribution of MgZn2 dispersions increases the strength. They also have seen that AA7075 with T6 temper is exposed to brittle fracture, which exhibit ductile failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, bulk of researches on the 7xxx alloys used commercial alloys [12][13][14], whereas RBC was suitable as a source of Al that can be converted to the 7xxx alloys by the addition of Zn, Mg, Mn and Cu. The effect of wt.% Zn addition of other grain refining elements, annealing and artificial ageing heat treatment parameters had been reported to affect the mechanical properties of 7xxx alloys [15][16][17]. The formation of secondary phases like the η(MgZn2), T(Al2CuMg), and S(Al2CuMg) were affected by the aforementioned parameters [15,18] as a result of the increase in the solute content around the vacancies [19].…”
mentioning
confidence: 99%
“…The effect of wt.% Zn addition of other grain refining elements, annealing and artificial ageing heat treatment parameters had been reported to affect the mechanical properties of 7xxx alloys [15][16][17]. The formation of secondary phases like the η(MgZn2), T(Al2CuMg), and S(Al2CuMg) were affected by the aforementioned parameters [15,18] as a result of the increase in the solute content around the vacancies [19]. Our analysis of the transformation of phases within the Guinier-Preston (GP) zones [20] in presented in Figure 1.…”
mentioning
confidence: 99%